Affidavit of Paul Leeland Kirk - Kirk, Paul L. (1955)
Dr. Paul Leeland Kirk, professor of Criminalistics, stated in his affidavit that he examined the crime scene, various pieces of evidence held by the prosecutor and police, and blood samples collected and mailed to him. His investigation began on January 22, 1955 and continued for several months. Dr. Kirk used blood spatter analysis to conclude that: 1. The murderer was left-handed (Sam Sheppard was right-handed) 2. From injuries to the victim's teeth, the victim had bitten the attacker's hand 3. A large bloodstain on the wardrobe door was likely from the attacker's bloody hand 4. Testing of the large blood stain showed it did not match that of Sam or Marilyn Sheppard, so the attacker must have been a third person 5. The murder weapon was a cylindrical object, such as a pipe or flashlight--not a a surgical instrument, as asserted by the Coroner Dr. Kirk surmised that the physical evidence demonstrated that the crime was a sexual assault